Structure and bioactivity of Ti/bioactive glass 'changing landscape coatings'. Issue 4 (1st December 2013) - Nelson, Greg M.; McDonald, AndrÉ G. André G.; Nychka, John A.
Abstract : Porous titanium alloy–bioactive glass composite coatings were produced via flame spray deposition. The porous coatings, targeted for bone fixation and orthodontic devices, were made from bioactive glass (45S5) powder blended with one of two titanium powders: commercially pure titanium (Cp-Ti) or titanium alloy (Ti-6Al-4V). The coatings were characterized by cross-sectional quantitative metallography, optical microscopy, scanning electron microscopy, Fourier transform infrared spectroscopy and X-ray diffraction. The porosity and glassy phase distributions were determined by image analysis of optical micrographs, in accordance with ASTM Standard E2109. Selection of Cp-Ti or Ti-6Al-4V alloy, along with alteration of the particle size distribution of bioactive glass, dramatically changed the morphology and phases present within each coating. The consequences on the bioactive response were characterized with immersion testing in simulated body fluid for up to 14 d. The coatings were analyzed for the presence of hydroxyapatite (HA) after testing; HA formation was observed as soon as 7 d for Ti-6Al-4V-based composites, while no formation occurred on Cp-Ti-based composites. HA formation on the negative Ti-6Al-4V control coating was observed after 14 d, while formation was not observed on the Cp-Ti coating, suggesting that the incorporation of bioactive glass into flame-sprayed Ti-6Al-4V alloy coatings enhances bioactivity.